2020
DOI: 10.1002/pip.3365
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory comparison of angular‐dependent photovoltaic device measurements: Results and impact on energy rating

Abstract: This paper presents the results from an extensive interlaboratory comparison of angular‐dependent measurements on encapsulated photovoltaic (PV) cells. Twelve international laboratories measure the incident angle modifier of two unique PV devices. The absolute measurement agreement is ±2.0% to the weighted mean for angles of incidence (AOI) ≤ 65°, but from 70° to 85°, the range of measurement deviations increases rapidly from 2.5% to 23%. The proficiency of the measurements is analysed using the expanded uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Furthermore, it shows that the RE increases with increasing AOI for most of the samples, while the RE of the gold and control sample at high AOI decreases to less than 1%. The differences of the RE at high AOI shows the strong influence of alignment errors in measurements, which is consistent with the observation in Riedel-Lyngskaer et al [44]. Therefore, the increased RE at a higher AOI can be the result from alignment errors in the lab or in the field.…”
Section: Short-circuit Current Simulationsupporting
confidence: 90%
“…Furthermore, it shows that the RE increases with increasing AOI for most of the samples, while the RE of the gold and control sample at high AOI decreases to less than 1%. The differences of the RE at high AOI shows the strong influence of alignment errors in measurements, which is consistent with the observation in Riedel-Lyngskaer et al [44]. Therefore, the increased RE at a higher AOI can be the result from alignment errors in the lab or in the field.…”
Section: Short-circuit Current Simulationsupporting
confidence: 90%
“…The module power matrix as shown in Table 2 is taken from [19]. The spectral response and angular behavior of module 2 are simulated using the Daidalos cloud ray tracer [20], which demonstrated good agreement with measurements in several studies [21]- [24]. The results shown in red in Figure 2.…”
Section: Test Module Input Datamentioning
confidence: 82%
“…We here recommend to use a least square fit optimization with measurement data and to limit to the range from 0° to 80° incidence angle. Measurements of higher incidence angles are increasingly prone to systematic measurement errors and therefore measurements at 85° should be rejected [24]. In the CSER calculation, the angular loss coefficient should be specified with an accuracy of five digits to prevent the impact of the fitting and rounding on the calculation.…”
Section: A Recommendations For the Aoi Correction Proceduresmentioning
confidence: 99%
“…Furthermore, nanotexturing by BS provides superior reflectance properties over a wide range of incidence angles compared with microtextured solar cells. [35][36][37] For example, Xie et al [35] tested the polarization and angular dependence of BS samples, which showed low reflectance up to a large angle of incidence of 80°. Davidsen et al [36] demonstrated that RIEnanotextured multicrystalline Si solar cells show a 3% point improvement in average-normalized angle-resolved power output compared to microtextured, and the nanotextured monocrystalline Si cells show above 1% point improvement compared to microtextured cells.…”
Section: Doi: 101002/pssr202200482mentioning
confidence: 99%